Information Overload and the Entrepreneurs' Behaviour: Mediating Role of Entrepreneurial Self-Efficacy. Issue 1 (June 2020) - Karia, Manisha; Bathula, Hanoku; Gaur, Sanjaya Singh
Undoubtedly, the entrepreneur is the key to the initiation of the entrepreneurial process and firm performance. Since entrepreneurs vary in their background and abilities, researchers have examined the factors impacting their performance. Previous results show that personality characteristics and self-efficacy of entrepreneurs had a positive impact on their performance. In this study, we consider that entrepreneurs' self-efficacy (ESE) is a multi-dimensional concept and identify six inherent dimensions. Further, we include two other variables that have not received adequate attention in the literature so far, namely, entrepreneurial information overload (EIO) and entrepreneurs' human resources management (HRM) behaviour. To undertake empirical analysis, we developed a conceptual framework that proposes a negative impact of entrepreneurial information overload on entrepreneurial self-efficacy and entrepreneurs' HRM behaviour. Responses from 403 entrepreneurs of a large emerging economy were subjected to path-based multiple regression analysis. The results reveal that information overload has a direct impact on all the ESE dimensions, except on planning tasks. Although there is no direct effect of EIO on entrepreneurs' HRM behaviour, there is an indirect effect through the mediating role of ESE. These results suggest the need for appropriate strategies to help entrepreneurs to deal with information overload and ways to improve specific dimensions of ESE as necessary. Further, this study provides a platform for empirical research for future studies.